High productivity of tree species planted outside their current geographic range indicates large regions of unrealized niche space - Griesbauer, Hardy; O’Neill, Gregory A.; MacKenzie, William H. (Frontiers in Plant Science, 2025)
IntroductionReforestation efforts that utilize assisted range expansion in response to climate change require an enhanced understanding of tree species’ fundamental niches as well as potential interactions with local species when planted in novel environments.MethodsUsing height-age modeling and dendrochronological approaches, we analyzed height and radial growth data from 25 disparate experimental plantings of three temperate zone conifer species (Douglas-fir, western larch and ponderosa pine) in environments north of, and colder than, their current geographic range in British Columbia, Canada, to explore how these types of trials can provide important insights into tree species’ fundamental niches in regions that lack comprehensive, replicated experiments.Results and discussionHeight growth of the three species exceeded or equaled that of populations growing within their realized niche, suggesting that from a growth perspective, the fundamental niches of these species have historically included environments colder and further north than their current ranges. The productivity of Douglas-fir and western larch also exceeded that of a local tree species, lodgepole pine, across a range of sites and climates within the study region, indicating that these species may be successful competitors with other species outside their range. Across all species and locations, environmental constraints on tree productivity appear to be more consistently related to available soil moisture than temperature. This study suggests that temperate conifers may have unrealized niche space far outside their current geographic range, and their potential for range expansion may be larger than suggested by species distribution models.